Upaya Meningkatkan Hasil Belajar Ekonomi Melalui Metode Tutor Sebaya Kelas Xi Madrasyah Aliyah Di Palangka Raya: Efforts to Improve Economic Learning Outcomes Through Sebaya Classroom Madrasyah Aliyah Classroom Tutors in Palangka Raya - Suyati, Endang Sri (Anterior Jurnal, 2014)
The subjects in this research are all the students on class XI IPS 1 MA Darul Ulum Palangkaraya that amount 22 students who at one time used as a sample. There is increased activity of learners in the learning economy by applying the method of peer tutoring in class XI IPS 1 MA Darul Ulum Palangkaraya be better, learners are more active and participate in the learning process, so that students are able to express their opinions both orally and in writing. There is the increasing of economy learning outcomes by implementing peer tutoring method in class XI IPS 1 MA Darul Ulum Palangkaraya. In the cycle I can be determined the percentage of pre-acquisition results of the test are learners who completed 18.18% (4 people) and students who did not complete 81.82% (18 people) with an average value is 49.27. As for the acquisition of the results of the cycle I of activity percentage of students is 72.72 % with an average of 28.28, while the acquisition of learning outcomes of students is 68.18% with an average of 60.68. In the cycle II of acquisition activity, the percentage of students is 90.9% with an average of 35.68, while the acquisition of learning outcomes of students is 95.45% with an average of 84.45. There is an increase in learning outcomes of pre-test to the cycle I is 50%, while from the cycle I to the cycle I there is an increase in learning outcomes as many as 27.27%.